2015
DOI: 10.1111/cas.12809
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of SYCP2 predicts early stage human papillomavirus‐positive oropharyngeal carcinoma: A prospective whole transcriptome analysis

Abstract: This study was designed to identify significant differences in gene expression profiles of human papillomavirus (HPV)‐positive and HPV‐negative oropharyngeal squamous cell carcinomas (OPSCC) and to better understand the functional and biological effects of HPV infection in the premalignant pathway. Twenty‐four consecutive patients with locally advanced primary OPSCC were included in a prospective clinical trial. Fresh tissue samples (tumor vs. matched normal epithelium) were subjected to whole transcriptome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 45 publications
(107 reference statements)
4
98
0
3
Order By: Relevance
“…Actually, c - MYC is typically amplified in HPV16 cervical squamous cell carcinomas [25, 26], and its binding to the consensus DNA element is reported to be methylation-sensitive, in particular at CpG islands and nearby regions, supporting our finding of an interaction at hypomethylated regions at CpG island shores [27, 28]. …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Actually, c - MYC is typically amplified in HPV16 cervical squamous cell carcinomas [25, 26], and its binding to the consensus DNA element is reported to be methylation-sensitive, in particular at CpG islands and nearby regions, supporting our finding of an interaction at hypomethylated regions at CpG island shores [27, 28]. …”
Section: Resultssupporting
confidence: 80%
“…3). In fact, a recent study describes that SYCP2 up-regulation predicts early stage HPV(16) oropharyngeal carcinomas [28]. Moreover, we identified a minimal epigenetic signature made of five CpGs encompassing three genetic loci (B3GALT6-SDF4, SYCP2-FAM127B and HTLF-HLTF-AS1) that showed a high specificity (>95%) in identifying HPV(+) cases, independent of the anatomic site.…”
Section: Discussionmentioning
confidence: 72%
“…6C). Hi-C and ChIA-PET linkages indicated that the region is within a TAD and validated a regulatory connection to the cancer-associated gene SYCP2 67 . We further observed strong binding of many TFs in this region in MCF-7.…”
Section: The Extended Gene Representationmentioning
confidence: 82%
“…Linkage to oesophageal cancer (Wu, Song, Pang, & Chen, ) and oropharyngeal squamous cell carcinomas (Masterson et al., )…”
Section: Discussionmentioning
confidence: 99%
“…The identification of saliva-derived mRNA in normal and cancer patients (Hu et al, 2008;Li et al, 2004) and other forensic applications (Juusola & Ballantyne, 2005) (Gibbs et al, 1993;Stemmler et al, 2009) Assessment of the regenerative potential of injured neurons (Starkey et al, 2009) m2 lnc-TET3-2:1 NONHSAT071649 A member of the ten-eleven translocation (TET) gene family, that plays a role in the DNA methylation process (Langemeijer et al, 2009) (Ragvin et al, 2010) Airway inflammation (Kuwahara et al, 2012) m7 FAM25A NM_001146157 Inflammation and infectious disease, decrease in immune response (Deloukas et al, 2004;Mauritz et al, 2010;Wang et al, 2014) m10 CRCT1 NM_019060 Linkage to oesophageal cancer (Wu, Song, Pang, & Chen, 2016) and oropharyngeal squamous cell carcinomas (Masterson et al, 2015) Early Alzheimer's disease-related stages (Parra-Damas et al, 2014) Promotion of tumour cell apoptosis and upregulation of the expression of apoptosis-related proteins (Wu et al, 2016) TA B L E 3 Description of functions and biological roles of validated exRNAs for gingivitis neutrophil, eosinophil and macrophage chemotaxis, etc.) and biological functions (antimicrobial activity, etc.)…”
Section: Discussionmentioning
confidence: 99%